Histogenesis of the Oesophagus of Guinea Fowl (Numida meleagris) at Prehatch and Posthatch - Innocent Jonah Gosomji; Sulaiman Olawoye Salami; James Oliver Nzalak; Muhammed Umar Kawu; Emmanuel Vandi Tizhe; Yilzem George Gurumyen; Edward Christopher Dung (Scientifica)
The histogenesis of the primordial oesophagus was studied to determine the period in which the tunics of the oesophagus developed and became functional in the helmeted guinea fowl (Numida meleagris). Eighteen embryos and nine keets were studied at prehatch and posthatch, respectively. Simple columnar epithelium surrounded by mesenchymal cells was obvious at the 8th day of embryonic development. By the 19th day of embryonic development, the four tunics, tunica mucosa, submucosa, tunica muscularis, and tunica adventitia/serosa, were beginning to differentiate from the mesenchymal cells and also the primordial oesophageal glands appeared as clusters of cells that invaginate from the epithelium. By the 27th day, the tunics were clearly differentiated and the primordial glands were fully developed as evident with positive reaction to Periodic Acid Schiff (PAS). The tunics of the muscularis were not well developed till at posthatch. This study therefore concludes that the primordial oesophagus is active at the late incubation due to mucin secretion by mucous glands but fully functional at posthatch since the tunica muscularis is completely developed at posthatch.